A185 ABDOMINAL WALL VARICES: A CASE REPORT. (26th February 2020) - Aruljothy, A; Russell, L; Nair, S; Albashir, S
Abstract: Background: Portal hypertension in cirrhosis results in variable and numerous portosystemic collateral circulations. Computed tomography (CT) and Doppler ultrasound (US) can identify these collateral vessels, especially abdominal wall varices, which can be encountered during a bedside paracentesis. Aims: Describe a case of traumatic abdominal wall variceal bleed. Methods: Case report. Results: A 53 year-old Caucasian male presented to the emergency department (ED) with 4-days of abdominal pain and 2-months of increased abdominal girth. His medical history included Child Pugh Class B alcoholic liver cirrhosis diagnosed 1 year ago. No prior history of ascites, esophageal variceal bleed or hepatic encephalopathy. In the ED, his US showed moderate ascites with right portal vein flow reversal. A diagnostic RLQ paracentesis showed yellow ascitic fluid, no spontaneous bacterial peritonitis (SBP), and he was discharged home with diuretics. He returned to the ED the next day for increased abdominal girth with a Hb of 103 g/L. A diagnostic RLQ paracentesis showed orange-red ascitic fluid and no SBP. The following day, a therapeutic US-guided paracentesis was attempted in the RLQ and left-lower quadrant LLQ; however, ascitic fluid aspirate was grossly bloody. The procedure was aborted. Hb was 82 g/L and progressively decreased. CT angiogram was performed and showed a 10.7 x 4.7 x 8.0 cm hyperdense fluid in the right paracolic gutter near the paracentesis site, consistent with intraperitoneal hemorrhage (Figure A). The insertion site was seen as abdominal wall musculature focal thickening around abdominal wall varices and no contrast extravasation was seen. Gastroesophageal, splenic hilar and omental varices were seen. Doppler US showed no sonographic signs of active extravasation. Interventional Radiology performed a US-guided paracentesis and aspirated 3650 mL of hemorrhagic fluid. Color Doppler US showed small varices within the subcutaneous soft tissues (Figure A). The patient later developed hematemesis with an EGD showing a large high-risk esophageal varix actively bleeding that was banded. Given the refractory variceal bleeding, a Minnesota tube was inserted 4 days later and a transjugular intrahepatic portosystemic shunt was inserted the following day. Unfortunately, the patient developed progressive worsening hepatic encephalopy, multi-organ failure and expired 7-days later. Conclusions: Adjunct imaging modalities such as color flow Doppler US or CT can be used as a screening tool to identify abdominal wall varices and reduce paracentesis bleeding complications. Funding Agencies: None